Annoying noise: effect of anthropogenic underwater noise on the movement and feeding performance in the red cherry shrimp, Neocaridina davidi - Azarm-Karnagh, Sasan; López Greco, Laura; Shafiei Sabet, Saeed (Frontiers in Ecology and Evolution, 2023)
Anthropogenic noise in marine and freshwater environments has increased dramatically, with a range of negative impacts and detrimental consequences on many aquatic animals across taxa. Benthic organisms, including many invertebrates, can sense underwater sounds, yet the responses they trigger in these organisms have received little attention. We conducted two laboratory-based experiments to investigate the effect of underwater sound playback on the movement behaviour and feeding performance of the red cherry shrimp Neocaridina davidi as a model of freshwater decapod. Movement speed decreased significantly upon opening the divider in both the sound and control treatments. However, there were no significant sounddependent changes overall between the control and sound treatments. The spatial distribution of shrimps in response to the sound treatment showed significant changes; shrimps spent more time at the farthest one-third position from the sound source. Feeding latency (latency to find food) also increased in the sound treatment compared to the control. Moreover, in terms of the number of successes and failures in finding the food source in the control treatment, significantly more shrimps succeeded in finding the food source. Besides, the number of revisits to the food source decreased in sound treatment compared to control and more shrimps were significantly distracted in sound treatment. Our study highlights the crustacean´s ability to receive human-made sound. Thus, they are prone to the impacts of anthropogenic noise, causing negative impacts on their movement-swimming activities, and feeding behaviour and exposing them to potential predator threats. Affecting foraging performance in this gregarious species may have detrimental impacts on their reproductive success and, subsequently unexpected fitness consequences.